THE EFFECT OF ZAKAT AND ECONOMIC VARIABLES ON POVERTY AND COMMUNITY WELFARE IN INDONESIA: A SIMULTANEOUS PANEL DATA ANALYSIS - Abdul Wahid Mongkito; Indra Nola; Rita Ardilla; Elsya Restalina; Trisno Wardy Putra; Gamsir; Alfian Toar (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the influence of zakat and several macroeconomic variables on poverty and welfare levels as measured by the Human Development Index (HDI) in provinces in Indonesia. This study employs a descriptive quantitative approach using secondary panel data from 34 provinces in Indonesia over a ten-year period (2014–2023). A simultaneous equation model is applied to capture the reciprocal relationship between poverty and welfare (HDI). The variables analyzed include zakat, economic growth, inflation, investment, and labor. The results show that zakat, economic growth, inflation, investment, labor, and HDI simultaneously have a significant effect on poverty across Indonesian provinces. Meanwhile, zakat, economic growth, investment, labor, and poverty significantly influence the HDI. Partially, zakat, investment, labor, and HDI have a significant negative effect on poverty, indicating their role in reducing poverty levels. In contrast, zakat, economic growth, investment, and labor have a significant positive effect on HDI, suggesting their contribution to improving welfare. Inflation has a significant negative effect on poverty, while poverty has a negative but statistically insignificant effect on HDI. This study is limited to provincial-level secondary data and selected macroeconomic variables over a ten-year period. Future research may include additional socioeconomic variables or extend the observation period. This study provides empirical evidence on the role of zakat as an Islamic social finance instrument in reducing poverty and improving social welfare in Indonesia.